2018
DOI: 10.1016/j.vaccine.2018.05.111
|View full text |Cite
|
Sign up to set email alerts
|

Adherence with and completion of recommended hepatitis vaccination schedules among adults in the United States

Abstract: Hepatitis vaccine adherence and completion in adults is suboptimal. As a result, the majority of adults initiating each series may not be receiving the full protective benefit of these multidose vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 13 publications
4
27
0
Order By: Relevance
“…In addition, similar to the present study, they found that older adults had better adherence rates. The earlier study of Nelson et al [20] in the US also found better adherence among older adult age groups and, for those adherent in all age groups, relatively long intervals between vaccine doses as in the present study and others [13].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In addition, similar to the present study, they found that older adults had better adherence rates. The earlier study of Nelson et al [20] in the US also found better adherence among older adult age groups and, for those adherent in all age groups, relatively long intervals between vaccine doses as in the present study and others [13].…”
Section: Discussionsupporting
confidence: 86%
“…Few studies have examined multi-dose vaccine series completion in general adult populations. The recent study of Trantham et al [13], designed similarly to the present study but using administrative claims data, reported somewhat higher, but still poor, rates of adherence in the US than in the UK, namely, rates of adherence to recommended schedules of 27, 30, and 18% for hepatitis A, hepatitis B, and hepatitis A/B, respectively. In addition, similar to the present study, they found that older adults had better adherence rates.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Although information regarding hepatitis A vaccination series completion rates is limited, low HAV vaccine series completion rates were observed among cohorts of commercial/Medicare (32%) and Medicaid (21%) enrollees in the United States (38). Additionally, adherence with and completion of recommended hepatitis vaccination schedules among adults in the United States have been described as suboptimal, leaving a substantial proportion of adults at risk (39). The same is true for adults in the United Kingdom, where adherence rates topped out at 23% (40).…”
Section: Discussionmentioning
confidence: 99%